PENERAPAN CASCADING BALANCE SCORECARD DALAM PEMBUATAN PETA STRATEGI TI (STUDI KASUS: DIREKTORAT SISTEM INFORMASI UNIVERSITAS 17 AGUSTUS 1945 SURABAYA) - Yusrida Muflihah; Agus Hermanto (INFORMAL: Informatics Journal, 2019)
The application of IT at the University 17 Agustus 1945 Surabaya has not received special attention because the role of information technology is only seen as a business supporter and not a major business. These conditions cause several problems related to the management of information technology at the University 17 Agustus 1945 Surabaya, namely: (1) the application of information technology governance is not optimal, (2) the function of information technology does not yet have a clear strategic and objective direction, (3) The role and employee responsibilities within the Information Systems Department are clearly defined. The purpose of this study is to create an information technology strategy map by applying the cascading balance scorecard process. In achieving the research objectives, ten cascading balance scorecard stages will be carried out, namely analyzing division objectives, identifying the relevance of divisions, identifying customer divisions, identifying division activities, tabulating outputs, identifying customer outcomes, lowering corporate strategy targets to the Division, compiling a strategy map, and determining KPI as well as strategic initiatives. The results of this study are IT strategy maps that show an increase in information technology user satisfaction that will lead to improved performance in conducting academic / non-academic operational activities. In support of increasing IT user satisfaction, IT mastery strategies are needed by all university human resources and enhancing relationships with IT vendors. Whereas in supporting the improvement of the performance of academic / non-academic operational activities, information systems and optimization of IT asset management need to be supported